Managerial economics - Maurice, S. Charles; Thomas, Christopher R. (Boston, Massachusetts : McGraw Hill Education, 1998)
The sixth edition of managerial economics continues to emphasize the economic way of thinking about business decision making.
Price determination in competitive markets -- Some preliminaries -- Demand : theory and empirical analysis -- Production and cost : theory and empirical analysis -- Perfect competition -- Firms with market power -- Risk and uncertainty
Includes index.
Keywords: ECONOMICS